Grameenphone Faces Problem in Rural Economy – A Case Study - Masoom, Muhammad Rehan (Ushus Journal of Business Management, 2021)
Telecommunication industry is one of the most dynamic and vibrant sectors, especially for the developing nations that have a huge population. However, unlike the developed nations, the infrastructure and the political scenario of the developing countries, indeed, posits various challenges.The expansion of multinational businesses requires becoming aware of not only the cultural differences, but the governances with proper emphasize. The case study deals with the recent SIM Tax issues and underlines the prospect of Mobile Operators‟ in the rural economy of Bangladesh